Children as treasures : childhood and the middle class in early twentieth century Japan - Jones, Mark A. (Mark Alan), 1969- (Harvard East Asian monographs ;, 2010)
Mark Jones examines the making of a new child's world in Japan between 1890 and 1930 and focuses on the institutions, groups, and individuals that reshaped both the idea of childhood and the daily life of children.